2022
DOI: 10.5662/wjm.v12.i4.285
|View full text |Cite
|
Sign up to set email alerts
|

Telehealth has comparable outcomes to in-person diabetic foot care during the COVID-19 pandemic

Abstract: BACKGROUND The coronavirus disease 2019 (COVID-19) pandemic has posed obstacles to the delivery of diabetic foot care. In response to this remote healthcare services have been deployed offering monitoring, follow-up, and referral services to patients with diabetic foot ulcers and related conditions. Although, remote diabetic foot care has been studied before the COVID-19 pandemic as an alternative to in-person care, the peculiar situation of the pandemic, which dictates that remote care would be t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2
2

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 26 publications
0
2
0
Order By: Relevance
“…Unfortunately, this study did not clearly mention the geographic location of the hospital in Haiti. More recently, Kamaratos-Sevdalis et al published a qualitative review of 12 English-language studies of telehealth services for diabetic foot infection from around the world [5]. Based on pre-established criteria, they selected five randomized trials, three case reports, three cohort studies, and one survey for analysis.…”
Section: Overview Of the Literature On Telemedicine In Haitimentioning
confidence: 99%
“…Unfortunately, this study did not clearly mention the geographic location of the hospital in Haiti. More recently, Kamaratos-Sevdalis et al published a qualitative review of 12 English-language studies of telehealth services for diabetic foot infection from around the world [5]. Based on pre-established criteria, they selected five randomized trials, three case reports, three cohort studies, and one survey for analysis.…”
Section: Overview Of the Literature On Telemedicine In Haitimentioning
confidence: 99%
“…17 Kamaratos-Sevdalis et al concluded that telemedicine can be applied effectively in diabetic foot care, and they noted that this method applied more effectively during COVID pandemics. 18 Elective and non-urgency surgical interventions have decreased worldwide due to COVID-19 restrictions and lockdown. In the previously published national cohort study, the pandemic group had a lower rate of limb salvage procedures such as debridement.…”
Section: Discussionmentioning
confidence: 99%
“…Kamaratos‐Sevdalis et al concluded that telemedicine can be applied effectively in diabetic foot care, and they noted that this method applied more effectively during COVID pandemics 18 …”
Section: Discussionmentioning
confidence: 99%